Political Participation and Authoritarianism: Interrelation and Differences Regarding Sociodemographic Variables - Noval Patallo, Noelia; Moral Jiménez, María de la Villa (Revista de Psicología, 2019)
The aim of this study was to relate political participation and authoritarianism, assuming that higher scores in authoritarianism would imply a lower degree of political participation. By incidental probabilistic selection it is obtained a sample of 233 volunteer participants aged between 18 and 73 years old (M = 32.86; DT = 14.085). The results provide empirical evidence on the significant differences in the factor “authoritarian aggression” of the Right Wing Authoritarian scale (RWA), assuming an inverse relationship with political participation. No gender differences were found in political participation, although they were found regarding to age, where higher participation scores were obtained in people over 46 years old. Likewise, significant differences were found in the “electoral” dimension of the Participation Behavior Questionnaire (CCP), in relation to the level of studies, considering higher levels of electoral participation when the educational level is higher. In addition, empirical evidences have been found pointing to higher scores of authoritarianism in people positioned on the right side of the political spectrum. The implications of the results obtained are discussed and the future research lines are outlined in the subject.